New Soliton Solutions of Fractional Jaulent-Miodek System with Symmetry Analysis - Sahoo, Subhadarshan; Ray, Santanu Saha; Abdou, Mohamed Aly Mohamed; İnç, Mustafa; Chu, Yu-Ming (Mdpi, 2020)
New soliton solutions of fractional Jaulent-Miodek (JM) system are presented via symmetry analysis and fractional logistic function methods. Fractional Lie symmetry analysis is unified with symmetry analysis method. Conservation laws of the system are used to obtain new conserved vectors. Numerical simulations of the JM equations and efficiency of the methods are presented. These solutions might be imperative and significant for the explanation of some practical physical phenomena. The results show that present methods are powerful, competitive, reliable, and easy to implement for the nonlinear fractional differential equations.
Keywords: fractional Jaulent-Miodek (JM) system; fractional logistic function method; symmetry analysis